Metal-free di- and tri-fluoromethylation of alkenes realized by visible-light-induced perylene photoredox catalysis. Issue 9 (20th July 2017) - Noto, Naoki; Koike, Takashi; Akita, Munetaka
Abstract : A new electrophilic CF2 H reagent and metal-free photocatalytic di- and tri-fluoromethylation by perylene were developed. Abstract : Regioselective amino-difluoromethylation of aromatic alkenes via C(sp 3 )–CF2 H and C(sp 3 )–N bond formation with the CC moiety has been achieved in a single operation by visible-light photoredox catalysis. The combination of a shelf-stable and easy-to-handle sulfonium salt, S -difluoromethyl- S -di( p -xylyl)sulfonium tetrafluoroborate, and perylene catalysis is the key to the successful transformation. Furthermore, this noble metal-free protocol allows for the photocatalytic trifluoromethylation of alkenes.